PENILAIAN EKONOMI DAN ANALISIS BIAYA MANFAAT AKTIVITAS SEKTOR INFORMAL DI KOTA BANDUNG Studi Kasus Beberapa Pasar Kaget - Muljarijadi, Bagdja (Indonesian Journal of Socio Economics)
This study aims to analyze some social economic aspects of informal sector activities using case study of pasar kagets in Bandung Municipality. The objectives are to give some description of the information we collected during the field survey, and give some reports on and analyze the Willingness to Pay (WTP) and the Willingness to Accept (WTA) of people who are doing informal business in the flea markets (pasar kaget) under study on some services. We use Censored Regression Model to estimate WTP and WTA for some relevant services in the pasar kaget. Base on benefits cost analysis (BCA) we found that average individual costs from pasar kaget is larger than its benefits.